ENHANCING SOIL HEALTH THROUGH BIOCHAR: A COMPREHENSIVE REVIEW - HASHIM ABUBAKAR, SAFIYANU; Nabayi, Abba (FUDMA JOURNAL OF SCIENCES, 2025)
Biochar has a beneficial importance on agricultural prosperity, according to various studies, the key dispute presently is how to maximize that important. It is important to maintain a significant content of organic matter in the soil for maintaining physical, chemical and biological sustainability of the soil and for suitable agricultural productivity. Improving the soil and biomass is estimated at the international level to enhance soil productiveness, fertility and to mitigate climate change. Appropriate use of agricultural waste as biomass by converting it as a useful source of soil organic amendments is one way to manage soil health and fertility. Agro-waste residues are partially utilized or un-utilized due to various constraints. Residue burning traditionally provides a fast way to clear the agricultural field of residual biomass, facilitating further land preparation and planting. However, in addition to loss of valuable biomass and nutrients, Agro-waste biomass burning leads to release of toxic gases including Greenhouse gases. Biochar is attracting a great deal of attention. Its characteristics of chemical, physical and biological properties, containing large surface area, Cation Exchange Capacity, high water-holding capacity, pore size, volume, distribution, and element composition, affect its recognized influences, particularly on microbial communities. Application and utilization of biochar in agricultural scope, forestry production, environmental protection and additional areas, has interested awareness by scientists and investigators inside and outside the country. Use of biochar in agricultural systems is one viable option that can enhance natural rates of carbon sequestration in the soil, reduce farm waste and improve the soil quality.
Keywords: Review; Significant; Biochar; Soil Health; Enhancing